PENETAPAN KADAR VITAMIN C PADA DAGING BUAH CABAI MERAH KERITING (Capsicum annum L.) YANG BEREDAR DI PASAR BUAH BERASTAGI KABUPATEN KARO MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - purba, jhan saberlan; elia, Sofia; Barus, Lidia Klorida (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Background: Vitamins are complex compounds that are needed by the body that function to help regulate or regulate the body's metabolic processes. One of the vitamins needed by the body is vitamin C. Vitamin C is a nutrient that acts as an antioxidant and is effective in overcoming free radicals that can damage cells or tissues, including protecting the lens from oxidative damage caused by radiation. Vitamin C or ascorbic acid is one of the vitamins that is soluble in water, easily oxidized, and sensitive to light stimulation. One of the plants that contain vitamin C is curly red chili. Red chilies have different levels of spiciness. Determination of vitamin C levels in red chili was carried out by UV-Vis spectrophotometry. This study aims: to determine the levels of vitamin C contained in the flesh of curly red chili (Capsicum annum L.) circulating in the Berastagi fruit market, Karo Regency. Methods: The sample used was curly red chili meat obtained from Berastagi fruit market, Karo Regency. The test was carried out by UV-Vis spectrophotometry with a wavelength of 296 nm. Results: The results of research conducted by UV-Vis spectrophotometry obtained an average level of vitamin C in the flesh of red curly chilies of 5.4689 mg/g. Conclusion: The results of the study showed that the flesh of curly red chilies had vitamin C.